49.1: Invited Paper: Opportunities of Liquid Crystal Polarization Holograms in Augmented and Virtual Reality Optics & Display Systems. (26th August 2021) - Lu, Lu; Masood, Taha; Silverstein, Barry
Abstract : This paper discusses the opportunities for Liquid Crystal Polarization Holograms (LCPHs) in Augmented Reality (AR) and Virtual Reality(VR) Optics & Display Systems, and how do we commercialize this this LCPH technology? We invite lithography tool vendors, liquid crystal material suppliers and LCD manufacturers to work together with us to enable the adaptation of this promising and transformational LCPH technology in the AR/VR field and beyond.